Amply (weakly) Goldie-Rad-supplemented modules - Mutlu, F.T. (Algebra and Discrete Mathematics, 2016)
Let R be a ring and M be a right R-module. We say a submodule S of M is a (weak) Goldie-Rad-supplement of a submodule N in M, if M=N+S, (N∩S≤Rad(M)) N∩S≤Rad(S) and Nβ∗∗S, and M is called amply (weakly) Goldie-Rad-supplemented if every submodule of M has ample (weak) Goldie-Rad-supplements in M. In this paper we study various properties of such modules. We show that every distributive projective weakly Goldie-Rad-Supplemented module is amply weakly Goldie-Rad-Supplemented. We also show that if M is amply (weakly) Goldie-Rad-supplemented and satisfies DCC on (weak) Goldie-Rad-supplement submodules and on small submodules, then M is Artinian.